Phenotypic and Molecular Characterizations of Streptococcus Spp. Isolated From Bovine Mammary Glands - Mian, Md. Firoz (2001)
Sixty-two streptococcal isolates comprising 20 Streptococcus agalactiae, 18 S. dysgalactiae and 24 S. uberis isolates were recovered from clinical and subclinical cases of bovine mastitis from different dairy herds in the Selangor state in Malaysia. A simple biochemical test scheme formulated on the basis of seven biochemical reactions allowed the identification of S. agalactiae, S. dysgalactiae and S. uberis isolates within 24 hours. Streptococcus agaJactiae isolates were l3-haemolytic, CAMP positive, utilized hippurate, salicin and raffinose; S. dysgalactiae isolates were a-haemolytic and fermented only trehalose and raffinose, while S. uberis isolates showed positive reactions to esculin, inulin and mannitol. The API 20 Strep System characterized accurately 100% of S. agalactiae and S. dysgalactiae isolates, and 96.1% of S. uberis isolates although some variable reactions among the isolates within the species were observed. Majority of the isolates were susceptible to most of the antimicrobial agents tested. All S. agalactiae, S. dysgalact;ae and S. uberis isolates were susceptIble to oxacillin and nitrofurantoin, while 30% of the isolates were resistant to tetracycline. Most of the S. dysgalactiae isolates showed resistance to kanamycin and cephalexin, and S. aga/actiae isolates to knamycin. Streptococcus dysgalactiae isolates showed higher level of resistance compared to S. agalactiae and S. uberis. Serotyping of the streptococcal isolates using monospecific antisera in agar gel double immunodiffusion revealed that all S. agolactiae isolates were typeable and demonstrated the type patterns II (60%), Ia (20%), III (15%) and IV (5%). On the other hand, 17 (94.4%) S. dysgalactiae and 22 (91.6%) S. uberis isolates were also identified. The SDS-PAGE and Western-blotting analyses revealed antigenic heterogeneity among the isolates of the bovine Streptococcus species examined. Sodium dodecylsulphate polyacrylamide gel electrophoresis could differentiate the three streptococcal species on the basis of their characteristic polypeptide bands. The Western blot analysis also revealed obvious differences in immunogenic proteins between the streptococcal species. Moreover, isolates within each species produced variable protein bands on PAGE analysis and variable immunogenic proteins by Western blotting which let the basis to group them into distinct PAGE and immunoblot fingerprint profiles respectively. Random amplified polymorphic DNA (RAPD) analysis was evaluated for its capacity to distinguish strains within the species of S. agalactiae, S. dysgalacliae and S. uberis and for epidemiological subtyping. Three single primers were used for each species to generate characteristic RAPD fingerprints. The DNA fingerprint patterns obtained with each primer were distinct and reproducible. The RAPD fingerprints generated could be useful in delineating the strains of S. agalactiae, S. dysgalactiae and S. uberis. The intraspecies typing efficiency was significantly improved by the parallel use of three primers. The RAPD results showed high level of genetic diversity within strains of the streptococcal species. The amplification of the DNA encoding 16S rRNA genes by polymerase chain reaction with single set of primers complementary to 16S rRNA gene regions generated characteristic single amplicon that enabled identification and differentiation of the three streptococcal species. The restriction fragment length polymorphism (RFLP) analysis of the amplified 16S rRNA gene regions with the restriction enzymes MspI and RsaI produced reproducible fingerprint patterns indicating high level of genetic diversity among the isolates of the streptococcal species. Higher heterogeneity was observed within S. uberis and S. dysgalactiae isolates than the S. agalactiae isolates. The discriminatory powers of the two enzymes were to some extent similar.